Dampak Pembelajaran Sistem Daring Terhadap Academic Fraud Pada Masa Pandemi - Yumna Rifdatul Ummah; Nurma Juwita (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2021)
The purpose of this research is to see the impact of learning using a bold system on the level of academic cheating that can be done by students. This research is a quantitative study using primary data. The data were obtained by distributing questionnaires to accounting students at the Muhammadiyah University of Surakarta. In the process of analyzing the data, the researcher used the incidental sampling technique. Incidental Sampling, is a technique where the researcher determines the research using the right principles. Where the researcher accidentally meets the respondent, and the respondent is matched by the researcher, the researcher makes the respondent a sample. Based on the results of data processing, it can be concluded that tcount 6.873> 1.655 t table and sig 0.00 <0.05 α. So, it can be ignored that the learning process has an effect on academic fraud. The results of this study are in accordance with the theory of diamond fraud which is related to the dimension of opportunity. In the dimension of diamond fraud, that someone is cheating because of opportunity. Students cheat during the learning process which is daring, because of supervisors from the problematic party.Keywords: Online Learning, Academic Fraud